(untitled) - Philander, Carlo

Distribution, mineralogy and provenance of heavy minerals in cainozoic sediments of the Namaqua Mines area, West Coast of South Africa (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.